Strategi Digital Branding dan Content Marketing berbasi Visual Literasi untuk Penguatan Identitas Produk UMKM Kota Serang - Neng Wiwin; Afifah Khaerani Aziz (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
The rapid development of the digital economy requires Micro, Small, and Medium Enterprises (MSMEs) in Serang City to transform from conventional marketing patterns to the digital realm. However, the main obstacles faced by partners are the weak visual identity of products and the low ability to manage attractive marketing content. This community service (PKM) activity aims to strengthen MSME product identity through mentoring on digital branding strategies and content marketing based on visual literacy. The implementation method was carried out through three stages: (1) conceptual workshops on branding; (2) technical training in creating visual content using digital design applications; and (3) mentoring in social media management. The results of the activity showed a significant increase in partners' understanding of the importance of visual aesthetics in building consumer trust online. Partners are now able to produce more professional independent content and have a consistent brand identity. The sustainability of this program is expected to accelerate the market expansion of Serang City MSMEs in the digital ecosystem